Quality improvement of green saba banana flour Steamed cake - Jau-Shya Lee; NurDiyana Yusoff; Ai Ling Ho; Chee Kiong Siew; Jahurul Haque Akanda; Wan Xin Tan (Molecular Diversity Preservation International (MDPI), 2022)
Gluten avoidance is becoming a popular diet trend around the world. In this study, green Saba banana flour (GSBF) was used to produce a gluten-free (GF) steamed cake. The effects of soy protein isolate (SPI) (0%, 10%, 15%) and Ovalette (0%, 3.5%, 7%) on the quality of the cake were investigated. Physicochemical properties of the flours were measured. The viscosity and specific gravity of the batters; as well as the specific volume, weight loss and texture profile of the resulting cakes were determined. Sensory evaluation was performed to compare the acceptance of the cake formulations. The macronutrient and resistant starch content of the cakes were determined. The use of an appropriate level of SPI and Ovalette was found to effectively enhance the aeration of the cake batter and improved the specific volume and weight loss of the cake. The presence of Ovalette was essential to soften the texture of the cake. GF cake supplemented with 10% SPI and 3.5% Ovalette obtained the highest sensorial acceptance. The nutritional quality of this sample was significantly improved, whereby it contained higher protein than the gluten-containing counterpart. GSBF also contributed to the high dietary fiber and resistant starch content of the cake..